Analysis of Social Media in Enhancing the Popularity and Reliability of Financial Statements Based on SAK EMKM - Trinanda, Muhammad; Nurbaiti, Nurbaiti; Nasution, Yenni Samri Juliati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to national economies, yet they face challenges with reliable financial reporting and low adoption of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Digital technology, especially social media, offers opportunities to enhance business visibility and financial transparency. This study analyzes social media's role in improving MSME popularity and financial statement reliability based on SAK EMKM. Using a descriptive qualitative approach, this study conducts a case study of MSME "dr. Kupi" in East Medan, collecting data via in-depth interviews and documentation. Findings indicate that strategic social media use, particularly on Instagram, significantly boosts popularity and community engagement through unique product promotion and interactive events. However, despite a high awareness of financial recording's importance and a partial transition to digital bookkeeping, a notable lack of familiarity with SAK EMKM challenges reporting reliability, although the owner is open to learning. This highlights a critical gap between digital marketing prowess and standardized financial management capabilities in the studied MSME.